Comparison of mental health and burnout between medical and nonmedical students - Valerie Carrard; Céline Bourquin; Sylvie Berney; Pierre-Alexandre Bart; Patrick Bodenmann; Alexandre Berney (PLoS ONE, 2025)
The high rates of mental health issues and burnout among medical students have been well established. Some suggest that these high rates are due to medical studies being particularly demanding compared to other undergraduate training. However, research comparing the mental health and burnout of medical and nonmedical students yields inconsistent findings and is limited by small sample sizes as well as infrequent consideration of potential confounding risk factors. This study aimed to complement past research by comparing the mental health and burnout of medical students to those of the nonmedical students at the same university, while accounting for confounding risk factors. A total of 1057 medical and 870 nonmedical students participated in the study, completing validated questionnaires measuring mental health (depressive symptoms, suicidal ideation, anxiety) and burnout (emotional exhaustion, cynicism, academic efficacy), as well as 14 risk factors pertaining to sociodemographic (incl. deprivation), lifestyle, psychological characteristics, life stress, and social relations. After conducting t-tests to compare the two groups, the impact of the risk factors was assessed with adjusted regressions. Results revealed that medical students reported significantly fewer depressive symptoms, suicidal ideation, anxiety symptoms, and cynicism than nonmedical students. They also presented fewer of the examined risk factors. After adjusting for these factors, medical students still exhibited lower suicidal ideation and cynicism, but all other differences became non-significant. Moreover, when accounting for risk factors, a new significant difference appeared, with medical students presenting more emotional exhaustion than nonmedical students. These findings suggest that medical studies are not inherently more taxing than other undergraduate disciplines. Both medical and nonmedical students face significant mental health challenges, likely reflecting the typical strains of young adulthood, exacerbated by the pressures of demanding studies. The results underscore the need for holistic interventions to support the mental well-being of all undergraduate students, regardless of their discipline or faculty.